Chromosome-level genome assembly of largemouth bass (Micropterus salmoides) using PacBio and Hi-C technologies - Kuo He; Liulan Zhao; Zihao Yuan; Adelino Canario; Qiao Liu; Siyi Chen; Jiazhong Guo; Wei Luo; Haoxiao Yan; Dongmei Zhang; Lisen Li; Song Yang (Scientific Data, 2022)
Measurement(s) genome assemble Technology Type(s) Illumina paired-end sequencing, PacBio single molecule sequencing technique (SMRT) and High-through chromosome conformation capture (Hi-C) technologies Sample Characteristic - Organism Micropterus floridanus